Bovine Ultra-Long CDR H3 Specific for Bovine Rotavirus Displays Potent Virus Neutralization and Therapeutic Effects in Infected Calves - Qihuan Zhao; Puchen Li; Bo Wang; Baohui Li; Min Gao; Guanyi Ren; Gege Rile; Saqi Rila; Ke Ma; Fuxiang Bao (Biomolecules)
Bovine rotavirus (BRV) is one of the main pathogens that cause acute diarrhea in calves under one month of age. Passive immunization has been recognized as an effective way to prevent and treat BRV infection. Recent studies have shown that 10% of bovine antibodies possess an ultra-long CDR H3 domain, which has been shown to be the smallest antigen-binding domain. Due to the extremely small size of ultra-long CDR H3 antibodies, the phage display method was utilized to obtain ultra-long CDR H3 antibodies targeting BRV, providing a new approach for the prevention and/or treatment of BRV. Here, we report the preparation of BRV-specific bovine ultra-long CDR H3 antibodies obtained by constructing and screening a phage display library containing approximately 8.55 × 109 individual clones. Through three rounds of bio-panning, we identified 92 candidate clones, of which 79 exhibited specific binding activity in phage ELISAs. The recombinant bovine ultra-long CDR H3 antibodies could specifically bind to BRV in ELISAs and cell immunofluorescence assays. The neutralizing activity was further confirmed through virus neutralization tests. In the calf model experiment, the recombinant bovine ultra-long CDR H3 antibodies could relieve the symptoms of diarrhea, reduce both the amount and duration of virus release, and increase the survival in calves experimentally infected with BRV. Therefore, BRV-specific bovine ultra-long CDR H3 antibodies could serve as an effective agent for the prevention and treatment of BRV infection. At the same time, the development of ultra-long CDR H3 antibodies using phage display screening technology provides a new approach for developing biological agents for the prevention and control of infectious diseases in bovines.